Short versus Standard Length Implants with Sinus Floor Elevation for the Atrophic Posterior Maxilla - Elk Schiegnitz; Nina Hill; Keyvan Sagheb; Jochem König; Kawe Sagheb; Bilal Al-Nawas (University of Zagreb. School of Dental Medicine, 2022)
Objectives: the aim of this clinical study was to compare clinical and radiological outcomes of short dental implants inserted in pristine bone to standard length implants inserted in combination with sinus floor elevation. Materials and methods: For this clinical study, the clinical and radiological outcome of 126 short dental implants (84 patients), inserted in pristine bone were compared with 312 standard length implants (156 patients), placed in combination with maxillary sinus floor elevation procedures. Results: The short implant group (test group [TG]; mean follow-up (± standard deviation (SD) 56.6 ± 42.9 months) and the augmented group (control group [CG]; mean follow-up 41.6 ± 37.6 months) showed cumulative survival rates of 91.8% and 92.4%. Cumulative 5-year implant survival rates were 91.8% for the TG and 90.7% for the CG (p=0.421). Mean marginal bone loss was significantly higher in the CG than in the TG, with a mean MBL of 0.70 ± 0.72 mm in the TG and 0.96 ± 0.91 mm in the CG (p<0.001). A comparable and promising oral health-related quality of life (OHRQoL) was observed in the control and test groups. Conclusions: After over 3 years, short implants placed in the resorbed posterior maxilla obtained similar results to standard implants combined with maxillary sinus floor augmentation procedures.